생명현상의 다양성과 특징에 관한 고찰 - 보건의료에 미치는 영향을 중심으로 - 이선동; Lee, Sun-Dong (대한예방한의학회지, 2010)
This research was intended to delve into the diversity of life phenomenon and its characteristics. First of all, this research gave real examples to compare the differences in men's health, disease, and longevity in order to confirm the existence of diversity of life phenomenon. In addition, it also studied the process and mechanism of manifestation of life phenomenon, as well as the influence and problems of existing studies' results and implications. The results are as follow. 1. Differences in health, diseases, and longevity were very big and diverse in researches on different races, nations, ages, socioeconomic status, positions, and even (monozygotic) twins. 2. The basic foundation of all organisms is DNA, and environmental factors change DNA methylation and the structure of chromatin by constantly influencing DNA. Due to this, the manifestation, control, and phenotype of DNA change, resulting in diversified life phenomenon. Therefore, it is the environmental factors, not DNA, that has more influence on the diversity of life. 3. Looking at available studies, the most reasonable perspective on human requires focusing on the diversity of life phenomenon, holistic thinking, and reversible change instead of irreversible determinism. Considerable differences in life phenomenon between entities require a change in malformed perspective on life. Public health and medicine deals with live human beings, a more precise and accurate perspective on life is very important. Because management methods of health and disease, such as structure and approaches of medical research, prevention and cure, must be different by life perspectives.